Evaluating the efficiency of desalination units in treating groundwater and their impact on the chemical balance of micro- and macro-elements – A case study: Selected areas in Tripoli (Al-Farooq Journal of Sciences, 2026)
This research aims to evaluate the efficiency of domestic desalination units in treating groundwater and to investigate the impact of these processes on the chemical balance and physicochemical properties of water in selected areas of Tripoli (Al-Hai Al-Sinai, Ain Zara, Souq Al-Jumaa, and Wadi Al-Rabie). The researcher employed an analytical experimental approach, collecting samples from four wells of varying locations and depths. A series of rigorous laboratory analyses were conducted before and after the desalination process, covering Hydrogen ion concentration (pH), Electrical Conductivity (EC), Total Dissolved Solids (TDS), and the concentrations of major cations (Sodium, Potassium, and Calcium).The research concluded that raw well water in most of the study areas suffers from severe salinity degradation exceeding permissible limits, particularly in the Ain Zara and Souq Al-Jumaa regions. The results demonstrated significant technical success of the desalination units in reducing total salinity, with removal rates exceeding 90%, thereby converting the water into a chemically fresh category. However, the results revealed a nearly complete mineral stripping of Calcium and Potassium, which dropped to non-detectable (ND) levels, along with a slight shift in pH values toward weak acidity.The study recommended the necessity of activating periodic monitoring of desalination units to ensure the retention of essential mineral elements and highlighted the importance of implementing remineralization processes to compensate for the deficiency in Calcium and Potassium for public health safety. Furthermore, it recommended expanding biological and spatial studies using Geographic Information Systems (GIS) to create contour maps illustrating the distribution of saline contamination within the regional aquifer.